2016
DOI: 10.3847/2041-8205/823/1/l5
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis of Interplanetary Solar Radio Emissions Associated With a Coronal Mass Ejection

Abstract: Coronal mass ejections (CMEs) are large-scale eruptions of magnetized plasma that may cause severe geomagnetic storms if Earth-directed. Here we report a rare instance with comprehensive in situ and remote sensing observations of a CME combining white-light, radio, and plasma measurements from four different vantage points. For the first time, we have successfully applied a radio direction-finding technique to an interplanetary type II burst detected by two identical widely separated radio receivers. The deriv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 43 publications
1
18
0
Order By: Relevance
“…The conclusion in section 4 regarding the type II radio emission being emitted at the second harmonic rests on the assumption that the source position of the type II radio emission is close to the CME nose. This is not necessarily the case, as many type II radio bursts have been reported to originate from the CME flank (e.g., Feng et al, 2013;Krupar et al, 2016;Magdalenić et al, 2014;Shen et al, 2013;Xie et al, 2012). Mäkelä et al (2018) were able to locate the radio emission source of the 6 July 2012 CME to the CME nose using radio Figure 9.…”
Section: Discussionmentioning
confidence: 99%
“…The conclusion in section 4 regarding the type II radio emission being emitted at the second harmonic rests on the assumption that the source position of the type II radio emission is close to the CME nose. This is not necessarily the case, as many type II radio bursts have been reported to originate from the CME flank (e.g., Feng et al, 2013;Krupar et al, 2016;Magdalenić et al, 2014;Shen et al, 2013;Xie et al, 2012). Mäkelä et al (2018) were able to locate the radio emission source of the 6 July 2012 CME to the CME nose using radio Figure 9.…”
Section: Discussionmentioning
confidence: 99%
“…However, the active region has been observed by STEREO-A/Sun Earth Connection Coronal and Heliospheric Investigation/Extreme Ultraviolet Imager (SEC-CHI/EUVI; Howard et al 2008). We have used the wavelet technique by Stenborg et al (2008) to produce a composite image for the 171Å and 195Å channels ( The favorable configuration of Wind and STEREO-A allows us to accurately locate the sources of the type III bursts by radio triangulation (Krupar et al 2014a(Krupar et al , 2016. We identified data points that correspond to peak fluxes for four pairs of frequency channels observed by Wind /WAVES (428 kHz, 484 kHz, 548 kHz, and 624 kHz) and STEREO-A/WAVES (425 kHz, 475 kHz, 525 kHz, 625 kHz) with signals above background levels.…”
Section: Type III Bursts Measurementsmentioning
confidence: 99%
“…Morosan et al (2014) have shown the low-frequency type III bursts at the expanding flank of a CME. Krupar et al (2016) analyzed the type II and type III bursts and concluded that the radio emission arises from the flanks of the CME. Electrons generating type III bursts are produced at magnetic reconnection with open, nearly radial magnetic field lines, along which the electrons propagate.…”
Section: Comparison Of Corpuscular and Radio Emissionsmentioning
confidence: 99%
“…Note that the applied fitting procedure is aimed only at formal interpolating and extrapolating of the observed bursts. For such a goal, we use a simple approximation that fits the radio data, while many other formal approximations could alsodo the job (for a pattern of non-formal, in-depth consideration, see, e.g., Krupar et al 2016). …”
Section: Associated Electromagnetic Emissionsmentioning
confidence: 99%